EMPLOYING ECOLOGICAL SYSTEMS THEORY TO EXPLORE THE INFLUENTIAL FACTORS ON EFL TEACHERS’ WELL-BEING IN THE PRIVATE SECTOR - Huynh Hong Nga, Ngo; Quoc Lap, Trinh (HNUE Journal of Science: Journal of Educational Science, 2025)
Drawing on ecological systems theory, this phenomenological study examines how contextual factors impact the well-being of EFL teachers at five private English language centers in the Mekong Delta region. Data were collected through narrative frames and semi-structured interviews. The findings revealed that the teacher well-being is complex and dynamic, shaped by multiple factors. Social and cultural factors (e.g., expectations from parents), organizational factors (e.g., workplace culture, institutional policies, and facilities), occupational factors (e.g., professional qualifications and teaching experiences), and personal factors (e.g., physical health and passion for the profession) all play significant roles. This research addresses a gap in the literature on the teacher well-being of teachers in Vietnam’s private English language teaching (ELT) sector and offers valuable applicable to similar educational contexts worldwide.